2009
DOI: 10.1159/000209382
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Inflammatory Bowel Disease among Children in Poland

Abstract: Background/Aims: The incidence of pediatric inflammatory bowel disease (IBD) in Western countries is on the rise. No prospective studies have been conducted on the epidemiology of pediatric IBD in Poland. The aim of the study was to define the characteristics of new pediatric IBD and assess the incidence of new IBD among children in Poland between 2002 and 2004. Methods: Patient records from 24 pediatric gastroenterology centers servicing the whole population of Poland were collected. IBD diagnosis was based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 91 publications
2
14
3
1
Order By: Relevance
“…We suggest that a comparison of these studies may be indicative of the loss of this gradient in European children and exceptions to that rule. In addition, these findings reporting low incidence rates in eastern Europe contrast with the findings of a previous study in Polish children that suggested that the incidence of UC was higher than that of CD (1.3 vs 0.8/100000 person-years)[48]. …”
Section: Discussioncontrasting
confidence: 94%
“…We suggest that a comparison of these studies may be indicative of the loss of this gradient in European children and exceptions to that rule. In addition, these findings reporting low incidence rates in eastern Europe contrast with the findings of a previous study in Polish children that suggested that the incidence of UC was higher than that of CD (1.3 vs 0.8/100000 person-years)[48]. …”
Section: Discussioncontrasting
confidence: 94%
“…A total of 2209 references were reviewed, resulting in 139 included studies7–145 from 32 countries (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…1). Of included articles, 39 (28.1%) reported IBD incidence and/or prevalence in children only8, 12–14, 16–18, 29, 31, 48, 49, 51, 53, 65, 68, 71, 72, 77, 79, 83, 84, 86, 92, 107–109, 111–113, 115–117, 124, 129, 134, 136, 137, 141, 145, while the remaining 100 (71.9%) reported rates of pediatric IBD within cohorts of children and adults. The methods used for case ascertainment varied significantly between studies.…”
Section: Resultsmentioning
confidence: 99%
“…Difficulties associated with unanimous classification of a significant part of colitis to a strictly defined group are a serious medical problem [5, 16]. Classification of chronic colitis inadequate to actual condition may negatively influence therapy and prognosis in this large, socially important group of civilisation diseases.…”
Section: Resultsmentioning
confidence: 99%